Role of Scheduled Commercial Banks in Financial Inclusion in India - et al., Dr.S.Anitha (International Journal of Advanced Science and Technology, 2019)
The world in the present scenario has realized that inclusive growth is attainable only if two pressing issues such as exclusion and inequality in accessing financial services are addressed properly. The philosophy which addresses these issues through provision of easy accessibility of financial services for all segments of the society, especially the weaker and vulnerable sections, at a reasonable cost and indiscriminate manner is financial inclusion (FI).  Banking sector demonstrates major role in bringing financially excluded people in to formal financial sector as policies of the government and Reserve Bank through financial inclusion plans. In this paper an attempt has been made to portray the role of Scheduled Commercial Banks in financial inclusion for the past five years and FI’s impact on GDP. The role of banks in financial inclusion is assessed through data such as number of bank branches, outlets, Basic Savings Bank Deposit Accounts  (BSDBA), Kisan credit cards etc. Similarly the impact of FI on Economic growth is examined through multiple regression analysis by taking into consideration the Number of Branches , credit deposit ratio as independent variables and GDP as dependent variable .  Positive and significant impact of number of bank branches on GDP and negative insignificant impact of Credit deposit ratio on GDP are observed as findings of the study.